2018
DOI: 10.1038/s41562-018-0309-4
|View full text |Cite
|
Sign up to set email alerts
|

Male antisocial behaviour in adolescence and beyond

Abstract: Male antisocial behavior is concentrated in the adolescent period of the life course, as documented by the curve of crime over age. This article reviews recent evidence regarding the hypothesis that the age-crime curve conceals two groups with different causes. Life-course persistent males show extreme, pervasive, persistent antisocial behavior from early childhood to adulthood. They are hypothesized to be rare, with pathological risk factors and poor life outcomes. In contrast, adolescence-limited males show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
318
0
24

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(369 citation statements)
references
References 103 publications
(107 reference statements)
27
318
0
24
Order By: Relevance
“…An interesting adolescent-specific pattern concerns the increase in risk-taking, sensation seeking, and novelty seeking, which is often interpreted as a normative pattern in the path toward autonomy and identity development (Crone, Duijvenvoorde, & Peper, 2016;Pfeifer & Peake, 2012). At the same time, deviant behavior such as substance abuse, aggression, and delinquency emerge in adolescence in a subset of individuals (Fairchild, Goozen, Calder, & Goodyer, 2013;Moffitt, 2018), but why and how this occurs is not yet well understood. Although research has shown consistent patterns in developmental changes in brain structure across adolescence (Herting et al, 2018;Mills et al, 2016;Tamnes et al, 2017), few studies examined how the developmental pathway to externalizing behavior is associated with changes in brain development.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting adolescent-specific pattern concerns the increase in risk-taking, sensation seeking, and novelty seeking, which is often interpreted as a normative pattern in the path toward autonomy and identity development (Crone, Duijvenvoorde, & Peper, 2016;Pfeifer & Peake, 2012). At the same time, deviant behavior such as substance abuse, aggression, and delinquency emerge in adolescence in a subset of individuals (Fairchild, Goozen, Calder, & Goodyer, 2013;Moffitt, 2018), but why and how this occurs is not yet well understood. Although research has shown consistent patterns in developmental changes in brain structure across adolescence (Herting et al, 2018;Mills et al, 2016;Tamnes et al, 2017), few studies examined how the developmental pathway to externalizing behavior is associated with changes in brain development.…”
Section: Introductionmentioning
confidence: 99%
“…Disruptive behaviors predict school dropout, truancy, school exclusion and are the most common reason for referral to special education and mental health services (Kim-Cohen et al, 2005;Department for Education, 2010). In the longer-term, antisocial behavior can lead to violence and criminal offending, unemployment, relationship instability, health problems and early mortality (Moffitt, 2018), In terms of economic burden, evidence indicates that the greatest cost of externalizing problems appears to be borne by education services (Snell et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Aggressive behavior has been shown to be strongly linked to peers' social influences, broad social and contextual factors, cultural approval of violence, or even a genetic predisposition, although parents are among the strongest influences on the development of aggressiveness in young people (Garcia, Lopez-Fernandez, & Serra, 2018;Moffitt, 2018;Raine, 2002). Many parenting studies generally identify two main orthogonal (i.e., unrelated) dimensions (responsiveness and demandingness, also called warmth/acceptance/ involvement and strictness/imposition) and four parenting typologies (i.e., authoritative, indulgent, authoritarian, and neglectful).…”
mentioning
confidence: 99%